PLANNING THE LEARNING PROCESS OF ISLAMIC EDUCATION (CASE STUDY OF FATMAWATI ISLAMIC KINDERGARTEN BOGOR) - Hendra, Ulumiah; Maemunah Sa'diyah (JPG: Jurnal Pendidikan Guru, 2024)
Learning activities are activities that are very necessary for everyone. Because through these educational activities individuals can develop well. If we talk about educational activities, we will probably be immediately interested in the educational activities that take place at school. We ask ourselves, how educational activities can be carried out effectively in schools, of course there are many elements that need to be considered for the implementation of effective learning activities. Some of them concern teaching staff, students, teaching media, teaching materials, learning strategies and planning educational activities. One of the most important elements in educational activities is a good learning plan. Planning basically defines the activities that need to be carried out in the future. The aim of this activity is to organize various resources so that the results obtained are in line with expectations.